Hand anthropometric study in northern Colombia (2017)
The main purpose of this study is to gather information about the dimensions of the northern Colombian (Caribbean region) population, focusing on the dimensions of the hand and comparing them with measurements from other regions. Thirty-two hand dimensions were chosen and 120 males and 86 females were measured. Results indicated that there were differences between the dimensions of the hand for men and women, showing that men are larger. Also, there was a comparison made between some measurements of other studies in different regions of Colombia, the USA, Chile, Jordan, Korea and Japan. The results indicated important physiological differences between regions in Colombia and across countries. It was therefore concluded that differences in anthropometric measurements must be included in the design and procurement of machinery and apparatus in order to avoid productivity loss, occupational injuries or illness. © 2016 Central Institute for Labour Protection–National Research Institute (CIOP-PIB).